1989
DOI: 10.2307/3809582
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Sex Ratios in Caribou: Maternal Age and Condition Effects

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 169.230.243.252 on Mon, 13 Apr 2015 07:57:25 UTC All use subject to JSTOR Terms and Conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 11 publications
3
24
0
Order By: Relevance
“…Kruuk et al (1999) found the proportion of red deer (Cervus elaphus) calves born each year that were males declined with increasing population density and winter rainfall, both environmental variables associated with maternal nutritional stress during pregnancy. Thomas et al (1989) also found support for the TW model among caribou (Rangifer tarandus pearyi and R. t. groenlandicus) with differential maternal condition. Conversely, several other studies of ungulates found female-biased offspring sex ratios when maternal nutrition was high (Hoefs and Nowlan 1994;Pederson and Harper 1984;Sachdeva et al 1973;Verme 1969).…”
Section: Discussionmentioning
confidence: 77%
“…Kruuk et al (1999) found the proportion of red deer (Cervus elaphus) calves born each year that were males declined with increasing population density and winter rainfall, both environmental variables associated with maternal nutritional stress during pregnancy. Thomas et al (1989) also found support for the TW model among caribou (Rangifer tarandus pearyi and R. t. groenlandicus) with differential maternal condition. Conversely, several other studies of ungulates found female-biased offspring sex ratios when maternal nutrition was high (Hoefs and Nowlan 1994;Pederson and Harper 1984;Sachdeva et al 1973;Verme 1969).…”
Section: Discussionmentioning
confidence: 77%
“…In sheep (Ovis aries) and sea otters (Enhydra lutris), younger females produce more female offspring than older animals (Kent 1992;Bodkin et al 1993). The picture is less clear for different populations of bison (Bison bison) (Rutberg 1986;Wolff 1988;Green and Rothstein 1991), reindeer (Rangifer tarandus) (Skogland 1986;Kojola and Eloranta 1989;Thomas et al 1989) and white-tailed deer (Odocoileus virginianus) (Verme 1969(Verme , 1983Caley and Nudds 1987). In red deer (Cervus elaphus), dominance was related to an increased proportion of male offspring, and dominance and body mass were positively related , 1984.…”
Section: Discussionmentioning
confidence: 99%
“…First, old females have lower reproductive potential and a higher mortality rate than young females (Thomas and Barry, 1990a, b). Second, from 1980 through 1987, 61% of calves produced by females one to three years old in the Beverly herd were female calves, whereas only 33% of calves produced by old females were females (Thomas et al, 1990). Those young and old age classes represented about 33.4% and 9.4% of females older than calves, and they produced 38.2% and 7.3% of sampled female calves (Thomas and Barry, 1990b).…”
Section: Discussionmentioning
confidence: 99%